2012
DOI: 10.1111/j.2042-7158.2012.01555.x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal delivery of insulin via the olfactory nerve pathway

Abstract: These results demonstrated that intranasal administration of labelled insulin targeted the CNS through the olfactory nerve pathway in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 22 publications
0
74
0
Order By: Relevance
“…Numerous previous studies regarding protein and peptide delivery to the CNS have indicated that proteins such as NGF (Chen et al, 1998;De Rosa et al, 2005), insulin (Francis et al, 2008;Renner et al, 2012;Shemesh et al, 2012), and IGF-1 (Fletcher et al, 2009;Liu et al, 2001;Thorne et al, 2004) preferentially enter the CNS through extracellular channels between the olfactory receptor neuron (ORN) axons and the olfactory ensheathing cells protecting them from the cribiform plate (Dhuria et al, 2010;Wu et al, 2008). As a result, it is probable that preferentially depositing substances onto the olfactory epithelium where ORN axons originate would increase the amount of D1-D2 interfering peptide delivered to the CNS while minimizing loss to the periphery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous previous studies regarding protein and peptide delivery to the CNS have indicated that proteins such as NGF (Chen et al, 1998;De Rosa et al, 2005), insulin (Francis et al, 2008;Renner et al, 2012;Shemesh et al, 2012), and IGF-1 (Fletcher et al, 2009;Liu et al, 2001;Thorne et al, 2004) preferentially enter the CNS through extracellular channels between the olfactory receptor neuron (ORN) axons and the olfactory ensheathing cells protecting them from the cribiform plate (Dhuria et al, 2010;Wu et al, 2008). As a result, it is probable that preferentially depositing substances onto the olfactory epithelium where ORN axons originate would increase the amount of D1-D2 interfering peptide delivered to the CNS while minimizing loss to the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, IN drug delivery can result in 100-fold increases in protein drug concentration in multiple brain regions (Dhuria et al, 2010). A number of proteins including insulin and nerve growth factor have been delivered effectively to the central nervous system (CNS) IN in both animals and humans (De Rosa et al, 2005;Renner et al, 2012;Shemesh et al, 2012). Some of the other advantages of IN drug delivery include the possibility for at-home use, multiple dosings a day, and its cost effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…This has been shown for insulin (Renner et al, 2012), Andrews et al, 2011 No hypoglycemic effect after removal of stratum corneum Peptide Delivery Systems orexin-A (Dhuria et al, 2009), and exendin (Banks et al, 2004). Hexarelin, a growth hormone-releasing peptide, was delivered to the brain using a cosolvent and n-tridecyl-b-D-maltoside for improving the peptide permeation and enabling 1.6-fold greater plasma concentrations compared with intravenous administration (Yu and Kim, 2009).…”
Section: A Development Challenges Of Peptide Delivery Formulationsmentioning
confidence: 99%
“…After nasal delivery, drugs are taken up by the olfactory cell through the olfactory mucosa and transported into the brain, including the olfactory bulb, nucleus, amygdale, and hippocampus, along the olfactory beam, avoiding the obstruction of BBB and making it relatively easier to enter the brain. 7,8 Serralheiro et al 9 found that the bioavailability of lamotrigine (LTG) in brain was 116.5% comparing intranasal administration with intravenous administration in mice. Through the nasal route, drugs can avoid the obstruction of the BBB and enter the brain relatively easily.…”
Section: Introductionmentioning
confidence: 99%